2020
DOI: 10.2174/1389557520666200429101053
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen: A Biologically Important Coumarin with Emerging Applications

Abstract: : Coumarin has a place with a class of lactones which are fundamentally comprising of a benzene ring fused to αpyrone ring, known as benzopyrones. It likewise has a conjugated framework with electron rich and good charge-transport properties. It is delivered by plants to shield themselves from predation as a chemical response. Despite the fact that, coumarins have been utilized in different products like cosmetics, additives, perfumes, aroma enhancers in various tobaccos and some alcoholic drinks their most re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…Regarding the phototoxic activities of some linear furanocoumarins, majorly psoralen, bergapten, and xanthotoxin [ 119 ], more investigations focusing on the effect and toxicity of OP could be of interest. Until now, several studies have reported the adverse effects of some furanocoumarins that are caused by undesirable interactions with certain drugs, particularly furanocoumarins rich in grapefruit [ 9 ], but no similar study has been performed to analyze OP, and indeed this can also be considered a futuristic research aim.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the phototoxic activities of some linear furanocoumarins, majorly psoralen, bergapten, and xanthotoxin [ 119 ], more investigations focusing on the effect and toxicity of OP could be of interest. Until now, several studies have reported the adverse effects of some furanocoumarins that are caused by undesirable interactions with certain drugs, particularly furanocoumarins rich in grapefruit [ 9 ], but no similar study has been performed to analyze OP, and indeed this can also be considered a futuristic research aim.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatographic investigation of Guizhi in our previous research [ 20 ] revealed that its bioactive substances are coumarin, cinnamic acid, cinnamaldehyde, and 2-methoxycinnamaldehyde. Coumarin has been used in various products and candidate drugs because coumarin compounds have high bioavailability and both antioxidant and anti-inflammatory properties [ 23 ]. Cinnamic acid and its derivatives (such as ferulic acid and cinnamic amide) have attracted substantial attention due to their antioxidative, anti-inflammatory, and neuroprotective properties [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that IA reversed phospholipid metabolism, glycerophospholipid catabolism, and arachidonic acid metabolism through HIF-1α/SREBP-1, revealing that lipid metabolism may be associated with the antineoplastic effects of IA on CRC. Psoralen is a kind of biologically important coumarin derived from the fruits of Psoralea corylifolia L., which has been shown to reverse the multidrug-resistance (MDR) of HCC ( Thakur et al, 2020 ). However, the low solubility and poor stability of psoralen limit its wide use.…”
Section: Applications Of Metabolomics For Medicinal Plants In Gastroi...mentioning
confidence: 99%